Comparison of refractive and visual acuity results after Contoura® Vision topography-guided LASIK planned with the Phorcides Analytic Engine to results after wavefront-optimized LASIK in eyes with oblique astigmatism - Brunson, Phillip; Mann, Paul M.; Mann, Paul Michael; Potvin, Richard (PloS one, 2022)
To compare visual acuity and refractive results between topography-guided laser in situ keratomileusis (LASIK) planned with the Phorcides Analytic Engine (PAE) to results after wavefront-optimized (WFO) LASIK in subjects with preoperative oblique astigmatism in their manifest refraction. This was a retrospective chart review of clinical results from eyes treated with topography-guided LASIK planned with PAE compared to eyes treated with WFO LASIK using the same Wavelight® excimer laser system. All included subjects had preoperative oblique astigmatism. Residual refractive error and visual acuity (uncorrected and corrected) were the measures of interest, at the visit closest to 90 days postoperative. A matched data set from 100 WFO and 97 PAE eyes was extracted from clinical records. At the postoperative visit the PAE group showed lower residual refractive cylinder (p = 0.04), uncorrected distance visual acuity (UDVA) (-0.06 PAE vs. -0.02 WFO, p < 0.01) and distance corrected visual acuity (CDVA) (p < 0.01). The percentage of eyes with a mean refraction spherical equivalent (MRSE) magnitude within 0.25 D and 0.50 D of plano was statistically significantly higher in the PAE group (p = 0.04 and 0.01, respectively). A statistically significantly higher percentage of eyes in the PAE group had UDVA better than or equal to -0.10 logMAR (20/16 Snellen, 36% vs 22%, p = 0.04). More eyes gained CDVA after surgery in the PAE group (53% vs 32%, p < 0.01). There were five enhancements in the WFO group versus none in the PAE group, a statistically significant difference (p = 0.03). Visual acuity and refractive outcomes after LASIK using PAE in eyes with oblique astigmatism in their preoperative refraction were statistically significantly better than those obtained when WFO treatment was used. The number of refractive outliers and the number of retreatments were also significantly lower with PAE treatment.